Light, Heat and Roadside Plants - Chaphekar, S. B.; Kulkarni, S. S. (Indian Forester, 1973)
In a city, road surfaces and surfaces of buildings reflect a large proportion of incident light which is harmful to eye. Plants on the other hand, absorb and transmit some of it and reflect much less, making the sunny conditions comparatively easier to endure. Some readings recorded on hot afternoons in Bombay city are given here.